Analysis Impact of Transfer Some Assets PT Tambang Timah to PT Timah (Persero) Tbk on The Performance and Efficiency PT Timah (Persero) Tbk - Mahdalena, Eva; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
The independence program's subsidiary company PT Timah (Persero) Tbk (PT Tbk) among others PT Tambang Timah (PT TT), which resulted in leasing transactions for buildings, machinery and equipment are charged by PT TT to PT Tbk for the use of buildings, machinery and equipment PT TT used by PT Tbk. PT Tbk is a tin ore mining company that lease the assets from its subsidiary (PT TT) in the form of 5 (five) dredges for tin mining operations based on mining permission (IUP) of PT Tbk with a total cost of lease per year is Rp. 40.202.862.562, - (include VAT) with a lease term of 5 (five) years. With the company's operational cost efficiency, then PT Tbk review if the cost of leasing this property is cheaper or more expensive than the assets purchased by PT Tbk from PT TT. Buying Option 5 (five) dredges can result efficiency with reduce cash out money amounting to Rp. 90.257.696.866,- and can improve the performance of PT Tbk is shoThe independence program's subsidiary company PT Timah (Persero) Tbk (PT Tbk) among others PT Tambang Timah (PT TT), which resulted in leasing transactions for buildings, machinery and equipment are charged by PT TT to PT Tbk for the use of buildings, machinery and equipment PT TT used by PT Tbk. PT Tbk is a tin ore mining company that lease the assets from its subsidiary (PT TT) in the form of 5 (five) dredges for tin mining operations based on mining permission (IUP) of PT Tbk with a total cost of lease per year is Rp. 40.202.862.562, - (include VAT) with a lease term of 5 (five) years. With the company's operational cost efficiency, then PT Tbk review if the cost of leasing this property is cheaper or more expensive than the assets purchased by PT Tbk from PT TT. Buying Option 5 (five) dredges can result efficiency with reduce cash out money amounting to Rp. 90.257.696.866,- and can improve the performance of PT Tbk is shown in the ROA ratio analysis projected in 2013 to 11%, ROI (11%), and ROE (15%). Implementation plan buying of 5 (five) dredges are Dredges 16 Kebiang, Dredges 20 Belitung 1, Dredges 21 Singkep 1, Dredges 11 Karimata and Dredges 7 Meranteh is expected in mid-2013, the company efficiency is soon realized. Thus, the funds already budgeted for the payment of taxes and interdistric transaction on lease 5 (five) dredges can be used to the five dredges maintenance costs itself. Keywords: Leasing-Buying, ROA, ROI, ROE.wn in the ROA ratio analysis projected in 2013 to 11%, ROI (11%), and ROE (15%). Implementation plan buying of 5 (five) dredges are Dredges 16 Kebiang, Dredges 20 Belitung 1, Dredges 21 Singkep 1, Dredges 11 Karimata and Dredges 7 Meranteh is expected in mid-2013, the company efficiency is soon realized. Thus, the funds already budgeted for the payment of taxes and interdistric transaction on lease 5 (five) dredges can be used to the five dredges maintenance costs itself. Keywords: Leasing-Buying, ROA, ROI, ROE.